3 Here's a novel idea: would participants in simulation engage and learn more if they could debrief themselves? here's a tool that may help. (17th November 2016) - Hall, AJ; Turner, J; Bygrave, C
Abstract : Background: Debrief after Medical Simulation is a crucial part of the learning process, 1 whilst courses to train up faculty are widely available such as "TeachSim". The role of the faculty is two-fold: run the scenario and facilitate the debrief. The debrief is the tool used to extract learning points from the participants and also allow an emotional offloading from the scenario's events. 1 Ordinarily it is the faculty who lead the debrief, despite it being the participant's agenda that needs to be addressed. Multiple adult learning models demonstrate learners will gain more from a scenario if they are actively engaged in it, whilst it has also been shown anaesthetic trainees improved their non-technical skills by self-debriefing. 2 We propose that providing a tool to help the participant's debrief would improve their learning experience. Description of innovation: We have identified the role for a human factors tool to help engage learners in the debrief. Before a scenario we would introduce the tool – a collection cards listing human factors topics such as 'Communication', 'Teamwork' and 'Situational Awareness' each with example questions to ask in the debrief. Handing out a selection of the cards would focus those watching a scenario and facilitate them to ask questions of their peers in the debrief. Anticipated outcomes: We anticipate that the creation of a tool would benefit debriefing by educating participants about human factors as well as engaging them to have a greater role within the debrief which has been shown to improve learning. 1 We have started to collect data on this, which supports our theory. Potential impact: Facilitating a debrief can be the most difficult aspect for Simulation faculty. Educating participants to reduce their "blind spot" could allow them to explore and guide their own debrief, 3 thus maximising its effect.